2010
DOI: 10.1097/brs.0b013e3181d53724
|View full text |Cite
|
Sign up to set email alerts
|

Chromium Ion Release From Stainless Steel Pediatric Scoliosis Instrumentation

Abstract: Raised serum chromium levels were detected in 37% of patients following instrumented spinal arthrodesis for correction of scoliosis. This new finding has relatively unknown health implications but potential mutagenic, teratogenic and carcinogenic sequelae. This is especially concerning with most scoliosis patients being adolescent females with their reproductive years ahead.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Studies of metal ion levels in patients with spinal implants are less numerous. There have been only a few retrospective reports of metal ion levels in patients with stainless steel [18][19][20][21][22] and titanium [23,24] posterior spinal instrumentation. Less is known for metalon-metal total disc arthroplasty [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of metal ion levels in patients with spinal implants are less numerous. There have been only a few retrospective reports of metal ion levels in patients with stainless steel [18][19][20][21][22] and titanium [23,24] posterior spinal instrumentation. Less is known for metalon-metal total disc arthroplasty [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in tooth implants, this practice enables osteointegration, prevents infection, and increases the soundness of the implant material. Nickel, cobalt, titanium, chromium, silver, aluminum, and vanadium, as well as alloys of these metals, are often used in the coating [12][13][14][15][16][17]36]. However, any size particles of metals can dissolve in body fluids to form metal ions.…”
Section: Discussionmentioning
confidence: 98%
“…the implant material after implantation. Previously, serum levels of titanium, nickel, chromium, niobium, and aluminum were reported to be elevated in some implantation conditions [12][13][14][15][16][17]. In addition, boron mine has been reported to increase bone strength when used as dietary supplement [18][19][20].…”
Section: Introductionmentioning
confidence: 98%
“…Also concerning, recent studies have demonstrated elevated chromium levels in patients who have had fusion with stainless steel implants 73 and that these levels appear to be related to the amount of material used during fusions 74 . The implications of higher chromium levels are unknown, but high levels in animals have carcinogenic and mutagenic effects.…”
Section: Spinementioning
confidence: 99%